2010
DOI: 10.1111/j.1365-2818.2009.03228.x
|View full text |Cite
|
Sign up to set email alerts
|

TEM studies of plasma nitrided austenitic stainless steel

Abstract: Summary Cross‐sectional transmission electron microscopy and X‐ray phase analysis were used to study the structure of a layer formed during nitriding the AISI 316L stainless steel at temperature 440°C. It was found that the applied treatment led to the formation of 6‐μm‐thick layer of the S‐phase. There is no evidence of CrN precipitation. The X‐ray diffraction experiments proved that the occurred austenite lattice expansion – due to nitrogen atoms – depended on the crystallographic direction. The cross‐sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 6 publications
(8 reference statements)
3
16
0
Order By: Relevance
“…structure. These forbidden spots have been reported in previous studies (Meletis et al, 2002;Lei, 1999;Stró ż & Psoda, 2010;Jiang & Meletis, 2000), and are possibly due to N atoms at specific octahedral sites (Meletis et al, 2002;Stró ż & Psoda, 2010;Jiang & Meletis, 2000). The spots identified by the black spots in Figs.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…structure. These forbidden spots have been reported in previous studies (Meletis et al, 2002;Lei, 1999;Stró ż & Psoda, 2010;Jiang & Meletis, 2000), and are possibly due to N atoms at specific octahedral sites (Meletis et al, 2002;Stró ż & Psoda, 2010;Jiang & Meletis, 2000). The spots identified by the black spots in Figs.…”
Section: Resultssupporting
confidence: 81%
“…Such layers contain nitrogen ranging from about 10 to 35 at.% in the austenite matrix, and consist of a single phase named N (Williamson et al, 1994). The crystallographic features of the phase have been studied by X-ray diffraction (XRD) (Ö ztü rk & Williamson, 1995;Bacci et al, 2001;Meletis et al, 2002;Fewell et al, 2000;Sun et al, 1999;Fewell & Priest, 2008) and transmission electron microscopy (TEM) (Lei & Zhang, 1997;Xu et al, 2000;Lei, 1999;Mitchell et al, 2003;Stró ż & Psoda, 2010;Jiang & Meletis, 2000). However, the detailed atomic structure is controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to specify if these planar defects are micro-twins or systems of stacking faults, since both appear on 111 f gplanes [26,28]. Previous high-resolution electron microscopy investigations of the γ N phase report high densities of stacking faults with spacings between them sometimes less than few lattice planes [28,29]. In average one every sixth (111) plane contains stacking fault [26].…”
Section: Tablementioning
confidence: 97%
“…However, this does not appear to have been done in any of the above studies, although stacking faults have been observed in several TEM studies. Xu et al [26] and Stroz and Psoda [27] both examined the microstructure of plasma nitrided samples and observed stacking faults in the S-phase; the high-resolution image in the latter study showed stacking fault bundles with α~0.1. Nonetheless, they proposed the peak shift was due to a slight rhombohedral distortion in the lattice.…”
Section: Introductionmentioning
confidence: 98%